Immunosuppressive therapy and nutritional diseases of patients after kidney transplantation: a systematic review - Aleksandra Anna Kajdas; Marcin Kleibert; Anne Katrine Normann; Krzysztof Krasuski; Ditte Søndergaard Linde; Dorota Szostak-Węgierek (BMC Nephrology)
Abstract Background Kidney transplantation (kTx) is by far the most effective method of treating end-stage renal disease, with immunosuppressive therapy being obligatory for all, except identical twins. Despite kTx being the most effective treatment for end-stage renal disease, the patients face significant morbidity. They are often burdened with diabetes, anaemia, lipid disorders, all of which pose heightened risks for cardiovascular disease. Knowing that nutritional status plays a significant role in post-transplant results including graft survival, we conducted this systematic review with the aim to summarise the evidence of nutritional diseases following exposure to immunosuppressive therapy among patients after kTx. Methods This systematic review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist. Our search encompasses observational studies (cohort, case–control, cross-sectional) and randomized controlled trials (RCTs), published and unpublished, completed, and ongoing, written in English from the last 10 years (up to 17th February 2023) in the following databases: MEDLINE (via PubMed), EMBASE (Elsevier), Scopus and Web of Science. Any settings were eligible for inclusion. Quality assessments were done using ROBINS-I and RoB2 tools. Results were summarised in a narrative synthesis. Quantitative analysis was conducted where feasible. The protocol for proposed systematic review was published elsewhere. Results A total of 24 studies were included (participants n = 9,536) in the review. The majority of studies were cohort (n = 16), with moderate or low quality. Most of the studies (n = 16) were conducted in hospital settings. All studies had a higher proportion of male participants compared to female participants, except for one. Diabetes emerged as the most frequent disease assessed (n = 14), while tacrolimus (Tac) was the most commonly evaluated immunosuppressive medication used (n = 16). As a result, Tac presented a higher risk factor for the development of diabetes compared to cyclosporine (CsA). In addition, Tac was linked to weight gain in post-transplant recipients. In contrary, no relationship was found between steroids and weight gain. Regarding other immunosuppressants, everolimus was found to be associated with lipid abnormalities. Though, the relationship between lipid abnormalities and steroid use yielded inconsistent results. Calcineurin inhibitors (CNIs) were studied in various research articles. Consequently, patients who were not using CNIs had a lower prevalence of hypomagnesaemia, hyperkalaemia, and metabolic acidosis compared to those treated with CNIs. Also, CNIs were found to have a negative impact on 25-hydroxyvitamin D (25(OH)D) levels. Another aspect was the use of slow and fast Tacrolimus metabolizers. There was no difference observed in phase angle, visceral fat area, lean body mass index, and the proportion of lean mass as a percentage of total body mass between them. Finally, mammalian target of rapamycin (mTOR) inhibitors was associated with bone status and mycophenolate mofetil was linked to Vitamin B12 deficiencies. Conclusions To the best of our knowledge, this systematic review represents the first comprehensive overview of the evidence regarding immunosuppressive therapy and nutritional diseases in kTx patients. Our findings indicate an association between immunosuppressive therapy and nutritional diseases in this population. However, there is high heterogeneity and suboptimal quality of the included studies. Future researchers should prioritise high-quality, prospective randomized controlled trials to further elucidate these relationships. Trial registration PROSPERO (CRD42023396773), dated 12 April 2023. Protocol publication: https://doi.org/10.3390/jcm12216955 .